2005
DOI: 10.1016/s0002-9440(10)61210-2
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Signal Transducer and Activator of Transcription-1-Deficient Mice to Pulmonary Fibrogenesis

Abstract: The signal transducer and activator of transcription (Stat)-1 mediates growth arrest and apoptosis. We postulated that lung fibrosis characterized by excessive proliferation of lung fibroblasts would be enhanced in Stat1-deficient (Stat1 ؊/؊ ) mice. Two weeks after bleomycin aspiration (3 U/kg), Stat1 Pulmonary fibrosis is characterized by the excessive deposition of collagen in alveolar regions resulting in thickened alveolar septae and subsequent impairment of gas exchange. Lung fibroblasts are the central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 35 publications
3
57
0
Order By: Relevance
“…Alternatively, CXCL10 induces the production of IFN-␥ by lymphocytes in vivo in the lungs of mice (31). We have previously reported that STAT-1-deficient mice are susceptible to pulmonary fibrosis and this was correlated with a lack of growth inhibition in the presence of IFN-␥ in fibroblasts isolated from the lungs of STAT-1 null mice (10). Therefore, our findings support the hypothesis that STAT-1, IFNs, and CXCL10 are protective factors in the lung that limit the severity of a fibrogenic response and promote the resolution of fibrosis.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Alternatively, CXCL10 induces the production of IFN-␥ by lymphocytes in vivo in the lungs of mice (31). We have previously reported that STAT-1-deficient mice are susceptible to pulmonary fibrosis and this was correlated with a lack of growth inhibition in the presence of IFN-␥ in fibroblasts isolated from the lungs of STAT-1 null mice (10). Therefore, our findings support the hypothesis that STAT-1, IFNs, and CXCL10 are protective factors in the lung that limit the severity of a fibrogenic response and promote the resolution of fibrosis.…”
Section: Discussionsupporting
confidence: 87%
“…We recently reported that STAT-1 also acts in opposition to the stimulatory action of STAT-6 in promoting PDGF gene expression in response to IL-13 (9). Moreover, we discovered that mice deficient in STAT-1 have increased susceptibility to bleomycin-induced lung fibrosis, indicating that STAT-1 plays a protective role during fibrogenesis (10). Finally, we showed that V 2 O 5 is a potent activator of STAT-1 in lung fibroblasts (11).…”
Section: Stat-1 Signaling In Human Lung Fibroblasts Is Induced By Vanmentioning
confidence: 84%
See 1 more Smart Citation
“…Stat1 is also activated by IL-13 in a variety of lung cell types (10) and yet negatively regulates IL-13-induced signaling in pulmonary cell types (11)(12)(13). We recently demonstrated that Stat1-deficient (Stat1 Ϫ/Ϫ ) mice exhibited more severe pulmonary fibrosis after bleomycin injury compared with wild-type Stat1 ϩ/ϩ mice (14). Therefore, Stat6 and Stat1 are both important modulators of airway remodeling but appear to exert opposing biologic effects on cytokine signaling.…”
mentioning
confidence: 99%
“…TGF- is well known to be the principal factor that induces collagen gene expression, especially type I and type III collagen, and leads to tissue fibrosis through the cellular Smad signal transduction pathway (21)(22)(23). Smad2 and Smad3 are direct substrates of the TGF- receptor kinase, and interact with Smad4, which serves as a common signal mediator.…”
Section: Figure 4 Rt-pcr Results Of Type I Collagen (A and C) And mentioning
confidence: 99%